2019
DOI: 10.1088/1755-1315/389/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

The use of a MLP neural network for analysis and aodeling of land use changes with variations variable of physical and economic social

Abstract: Modeling the land use changes is a method that used to understand the causes and effects of dynamic changes. The model in this research is the ANN model with Multi-layer Perceptron (MLP) network architecture and backpropagation algorithm. The Artificial Neural Network (ANN) method is a potential method for land change as well as test the predictive abilities that will be produced by the model. Land use change modeling uses a combination of ANN and GIS methods. The aim of this research are (1) predict land use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This agrees with Heider et al (2018) andHernández-Flores et al (2017) who reported among the main urban driving forces distance to urban areas, distance to roads and population growth rate. But they did not agree with the findings of Akintuyi et al (2021), Fathizad et al (2019 and Subiyanto et al (2019), perhaps because they analysed other land-use changes in addition to urbanisation in countries with very different conditions from the study area.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This agrees with Heider et al (2018) andHernández-Flores et al (2017) who reported among the main urban driving forces distance to urban areas, distance to roads and population growth rate. But they did not agree with the findings of Akintuyi et al (2021), Fathizad et al (2019 and Subiyanto et al (2019), perhaps because they analysed other land-use changes in addition to urbanisation in countries with very different conditions from the study area.…”
Section: Discussionmentioning
confidence: 59%
“…It ranges from 0 (no association) to 1 (perfect association). Values close to 0.4 show an association between variables, and values less than 0.15 indicate a low association (Akintuyi et al 2021;Fathizad et al 2019;Subiyanto et al 2019). The independent factors used were elevation, distance to previous urban land, distance to roads, population density, education years, occupants per dwelling, percentage of the dependent population, percentage of indigenous households and land use.…”
Section: Driving Socio-economic Factorsmentioning
confidence: 99%
“…The MLP is one of the most popular neural network models in remote sensing thematic mapping. It has been widely used in land-cover mapping (Jamali 2020), land-use classification (Subiyanto et al 2019), and change detection (Wang, Lu, and Qin 2020). The MLP has the advantage of data-driven and automatic learning, which is conducive to specific classification tasks.…”
Section: Comparison With Other Benchmark Methodsmentioning
confidence: 99%